Enhancing Analytical Potential for Ultratrace Analysis of Inorganic Oxyanions Using Extraction Procedures with Layered Double Hydroxides - Ingrid Hagarová; Vasil Andruch (Toxics)
This article provides an overview of the use of layered double hydroxides (LDHs) as effective sorbents in various extraction methods, including column-based solid-phase extraction (SPE), dispersive solid-phase extraction (DSPE), and magnetic solid-phase extraction (MSPE), for the separation and preconcentration of inorganic oxyanions of chromium, arsenic, and selenium. The primary focus is on enhancing the analytical performance of spectrometric detection techniques, particularly in terms of sensitivity and selectivity when analyzing low concentrations of target analytes in complex matrices. LDHs, which can be readily prepared and structurally modified with various substances, offer promising potential for the development of novel analytical methods. When used in analytical extraction procedures and following careful optimization of experimental conditions, the developed methods have yielded satisfactory results, as documented by studies reviewed in this paper. This review is intended to assist analytical chemists in scientific laboratories involved in developing new extraction procedures.